Two-sided estimates of a solution of the Neumann problem as $t → ∞$ for a second-order Quasilinear Parabolic Equation - Tedeev, A. F. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
We establish exact upper and lower bounds as $t → ∞$ for the norm ‖u(·, t)‖ L ∞(Ω) of a solution of the Neumann problem for a second-order quasilinear parabolic equation in the region D=Ω×{>0}, where Ω is a region with noncompact boundary.